2014
DOI: 10.1155/2014/692423
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Care Model of Substance Use Treatment: What Works, and When Is “Enough,” “Enough?”

Abstract: There is little disagreement in the substance use treatment literature regarding the conceptualization of substance dependence as a cyclic, chronic condition consisting of alternating episodes of treatment and subsequent relapse. Likewise, substance use treatment efforts are increasingly being contextualized within a similar disease management framework, much like that of other chronic medical conditions (diabetes, hypertension, etc.). As such, substance use treatment has generally been viewed as a process com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 82 publications
0
33
0
Order By: Relevance
“…Moreover, the optimal length of stay may vary by the phase of treatment (Proctor & Herschman, 2014), level of treatment, type of substance and patient characteristics. For years, Washington State’s contracts with agencies had included a different performance measure, retention in outpatient treatment and many agencies may have viewed this retention measure as easier to achieve, since it required only one visit per month for three consecutive months and may have focused on the retention measure because it was in their contracts throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the optimal length of stay may vary by the phase of treatment (Proctor & Herschman, 2014), level of treatment, type of substance and patient characteristics. For years, Washington State’s contracts with agencies had included a different performance measure, retention in outpatient treatment and many agencies may have viewed this retention measure as easier to achieve, since it required only one visit per month for three consecutive months and may have focused on the retention measure because it was in their contracts throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized data from the Comprehensive Assessment and Treatment Outcome Research (CATOR) program . CATOR was designed as an assessment of program outcomes based on the collection of information related to patients' correlates of recovery and abstinence from all substances.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, clients are taught skills that promote a healthy lifestyle and specific coping skills that can be used after treatment to prevent relapse. Studies have shown that residential programs are effective as part of an overall theme of the length of time in treatment being associated with a better long-term outcome [4][5][6][7]. Unfortunately, most who do receive treatment suffer a high relapse rate which suggests there is still much to learn about the most effective treatment of SUDs.…”
Section: Introductionmentioning
confidence: 99%